Plasma creatinine as predictor of delayed elimination of high‐dose methotrexate in childhood acute lymphoblastic leukemia: A Danish population‐based study. Issue 6 (5th March 2019) - Schmidt, Diana; Kristensen, Kim; Schroeder, Henrik; Wehner, Peder Skov; Rosthøj, Steen; Heldrup, Jesper; Damsgaard, Linn; Schmiegelow, Kjeld; Mikkelsen, Torben Stamm
Abstract: Background: Severely delayed elimination of methotrexate (MTX) is difficult to predict in patients treated with high‐dose MTX (HD‐MTX), but it may cause life‐threatening toxicity. It has not been defined how an increase in plasma creatinine can be best used as a predictor for severely delayed MTX elimination, thus providing a guide for therapeutic interventions to minimize renal toxicity. Methods: Pharmacokinetic data were retrospectively collected on 218 Danish children with acute lymphoblastic leukemia treated with HD‐MTX 5 or 8 g/m 2 on the NOPHO2000 protocol. Moderately delayed MTX elimination was defined as 42‐hour plasma MTX ≥ 4.0–9.9 μM, and severely delayed elimination was defined as 42‐hour plasma MTX ≥ 10 μM. Results: Median 42‐hour plasma MTX was 0.61 μM (interquartile range, 0.4–1.06 μM). Of 1295 MTX infusions with 5 g/m 2 ( n  = 140 patients) or 8 g/m 2 ( n  = 78 patients), 5.1% were severely (1.5%) or moderately (3.6%) delayed. The risk of having delayed elimination was highest in the first of eight infusions with MTX 5 g/m² (7.4% vs 0.0 to 4.1% for subsequent MTX infusions) ( P  < 0.02). A 25 μM increase or a 1.5‐fold increase in plasma creatinine within 36 hours from start of the MTX infusion had a sensitivity of 92% (95% CI, 82%–97%) and a specificity of 85% (95% CI, 83%–87%) for predicting 42‐hour MTX ≥4.0 μM. Conclusions: A 25 μM increase or a 1.5‐fold in plasma creatinine within 36 hours after start of an HD‐MTX infusion can predict delayed MTX elimination, thus allowing intensification of hydration and alkalization to avoid further renal toxicity and promote the elimination of MTX.